On the hydrothermal behavior and entropy analysis of buoyancy driven magnetohydrodynamic hybrid nanofluid flow within an octagonal enclosure fitted with fins: Application to thermal energy storage. (September 2022) - Acharya, Nilankush
Abstract: Minimum entropy generation is usually considered a foremost criterion for an effective operation of the thermal storage system. Minimization of entropy is very significant because entropy minimization improves the proficiency of any device or system. The hydrothermal consequences of buoyancy-driven flow through the octagonal enclosure reveal major importance and those geometrical shapes are introduced in several technological and engineering applications like solar collectors, microfluidic heat sinks, nuclear power plants, heat exchangers, etc. Various types of fins are frequently operated in many devices or engineering fields related to electric transformers, heat exchangers, automobile radiators, gas turbines, air-cooled engines, semiconductor devices, hydrogen fuel cells, etc. Nanofluids disclose promising heat transport compared to traditional coolants. Furthermore, hybrid nanofluids are efficient and promising in heat transmission compared to usual nanofluids because of double metallic tiny particles' presence within the host medium. With this objective, the current study enlightens the hydrothermal conduct and entropy analysis of magnetized Ag-MgO-water hybrid nanofluid stream passing through the octagonal cavity and circular cylinder. Several rectangular heated fins are attached to the inner hot cylinder. The bottom and upper surfaces are heated, and vertically parallel walls are cold, whereas the inclined faces are made insulated. Similarity alternations are conducted to leading equations to have dimensionless profiles. The Galerkin-finite-element tactic has been merged to reconnoiter the solutions. Grid verification, assessment with the remaining works, and experimental verifications are completed to reveal the model's precision. Several velocities, streamlines, Bejan number, isotherms, entropy generation, and Nusselt number plots are addressed to expose the outcome of different fin lengths on the flow. Requisite diagrams are represented to unveil the parametric influences like nanoparticle concentrations (0.00 ≤ ϕ 2 ≤ 0.015), Rayleigh number(10 3 ≤ Ra ≤ 10 5 ), and Hartmann number (0 ≤ Ha ≤ 100). The analysis concludes that entropy increases for nanoparticle concentrations, and Rayleigh numbers, while the decrease is reported for the magnetic number. A similar impact is perceived for heat transport. Higher fins' length reduces the entropy. Highlights: The Ag-MgO-water flow enclosed within the octagonal cavity and circular cylinder is studied. The inner hot cylinder includes several rectangular fins having different lengths. Presence of magnetic field is assumed and entropy generation is analyzed. Entropy increases for Rayleigh numbers, and nanoparticle concentrations. Higher fins' length reduces the entropy.